Continuing Education Needs of Working Mechanical Diploma Engineers with Reference to Electronics and Computer Applications - Lal, Inder Mohan (Journal of Engineering Education Transformations, 1997)
This study conducted to determine continuing education needs of working diploma engineers in mechanical engineering with specific reference to Electronics and computer applications at work places. The study has revealed useful information from industry and working diploma holders for bridging the gap and making such diploma holders more useful to the industry.